2017
DOI: 10.1158/1541-7786.mcr-17-0095
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Cancerous Tissues Release Extrachromosomal Circular DNA (eccDNA) into the Circulation

Abstract: Cell-free circulating linear DNA is being explored for non-invasive diagnosis and management of tumors and fetuses, the so-called liquid biopsy. Previously, we observed the presence of small extrachromosomal circular DNA (eccDNA), called microDNA, in the nuclei of mammalian tissues and cell lines. Now, we demonstrate that cell-free microDNA derived from uniquely mapping regions of the genome is detectable in plasma and serum from both mice and humans and that they are significantly longer (30–60% >250 bases) t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
299
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 200 publications
(323 citation statements)
references
References 30 publications
20
299
4
Order By: Relevance
“…A study has shown that tumor specimens contain longer eccDNAs than normal lung tissues. Consistently, the circulating eccDNAs were longer in lung cancer patients collected prior to surgical resection of the tumor than in the same patient after surgery (37). Another study revealed that methotrexate (MTX)-treated human lymphoblastoid cells lines (LCLs) generated higher numbers of unique microDNA entities compared to non-treated cells.…”
Section: Implications Of Eccdnas In Human Diseases and Treatmentsmentioning
confidence: 84%
See 4 more Smart Citations
“…A study has shown that tumor specimens contain longer eccDNAs than normal lung tissues. Consistently, the circulating eccDNAs were longer in lung cancer patients collected prior to surgical resection of the tumor than in the same patient after surgery (37). Another study revealed that methotrexate (MTX)-treated human lymphoblastoid cells lines (LCLs) generated higher numbers of unique microDNA entities compared to non-treated cells.…”
Section: Implications Of Eccdnas In Human Diseases and Treatmentsmentioning
confidence: 84%
“…The enrichment is involved in exonuclease digestion (such as Plasmid-Safe-ATP-dependent DNase and/or exonuclease V) to remove linear DNA and multiple displacement amplification (MDA) to preferentially amplify circular DNAs (1, 3, 5, 6, 16, 27, 3638). This method has been proved to be effective for eccDNA detection and enrichment, especially when the initial DNA amount is very limited, for example the cell-free DNA (cfDNA) in the circulating system (27, 37). Other reported methods for eccDNA enrichment include multiple rounds of extensive exonuclease V digestion and chloride ethidium bromide density gradient centrifugation.…”
Section: Methods For Identification and Enrichment Of Eccdnasmentioning
confidence: 99%
See 3 more Smart Citations